Economic Empowerment Of Communities Impacted By The Earthquake In Cianjur, West Java Through Creative Stalls Based On Snack Food - Ade Vera Yani; Asep Dodo Murtado; Idealistuti Idealistuti (Universitas Muhammadiyah Palembang, 2024)
The earthquake in Cianjur with a magnitude of 5.6 magnetudos, was triggered by a shift in the new fault of the Cugenang Fault. As a result, 12 sub-districts in Cianjur Regency were affected. Residents' houses were damaged, ranging from minor damage to serious damage, resulting in casualties ranging from minor injuries, serious injuries to death. Cariu Village is one of the disaster locations with a large number of victims. 12 emergency tents from the Ministry of Social Affairs of the Republic of Indonesia became shelter for 350 heads of families with a population of 1,200 people. Post-earthquake economic life is a serious matter that should be of concern to all parties. The loss of jobs for some of the earthquake victims requires immediate action so that they can immediately get out of their burden. If it is allowed to drag on, it will have implications for poor social life, increasing levels of unemployment and poverty. The activity aims to empower people affected by the earthquake through creative food stalls based on local snacks. This activity is intended for earthquake victims who previously worked as food sellers. The activity begins with data collection on prospective program participants, motivational guidance and technical guidance, to calculating product selling prices. The result was that program participants recognized the family's economic recovery, grew in self-confidence and had hope for the future.